The North Atlantic Conoidean Gastropod Theta lyronuclea (Raphitomidae) in Deep-Waters of the Southwestern Atlantic - Sánchez, Noelia Carolina; Pastorino, Roberto Santiago Guido (Malacologia)
Theta lyronuclea (Clarke, 1959), a North Atlantic deep-water species, is recorded for the first time from the southwestern Atlantic. This constitutes the first record of the genus and the second mention of the family Raphitomidae off Argentina. The samples were collected in the Mar del Plata Submarine Canyon on the Argentine Continental slope on board the R/V Puerto Deseado at 2,934 m depth in September 2013. Photographs of radulae, penises, and details of the ornamentation of the protoconch are provided. Detailed comparison of the specimens collected with the type material and several lots from northern Atlantic localities confirmed the identification. Fil: Sánchez, Noelia Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina